“Making My Prayer with Joy”: Epistolary Prayer as Emotional Practice in Philippians and 1 Thessalonians - Schellenberg, Ryan S. (Novum Testamentum, 2022)
Drawing on recent literature in the history of emotions, this article describes Paul’s epistolary prayers as emotional practices that aim to harmonize and amplify the emotions of Paul and his addressees, particularly shared joy and longing. In Philippians and 1 Thessalonians, philophronetic topoi and the emotional norms they encode provide the basic cultural logic undergirding these prayers’ affective work. Compensating more or less successfully for the somatic signals otherwise constitutive of collective emotions, Paul’s explicit evocation of presumptively shared emotion nourishes the fantasy of presence and thus the rewards of common feeling, which include emotional sustenance for Paul himself and, if his letter is successful, a renewed feeling of solidarity among his addressees that reinforces their shared loyalty to Paul and his Lord.